Impact of the COVID-19 pandemic on Malaysian and Indonesian educators in tertiary institutions - Chew Chiou Sheng; Khyrina Airin Fariza Abu Samah; Fadilah Ezlina Shahbudin; David Loh Er Fu; Heni Mulyani; Nugraha Nugraha (Institute of Advanced Engineering and Science, 2023)
This study investigated the challenges encountered by educators conducting online teaching during the COVID-19 pandemic in Malaysian and Indonesian higher learning institutions. Quantitative and qualitative methods were used to obtain information in this study. The respondents comprised 250 educators from Malaysian and Indonesian higher learning institutions. A self-developed Likert-scale online questionnaire was given to the respondents. The study findings revealed that Malaysian educators faced greater challenges in mental health, time management, and assessments. In comparison, Indonesian educators experienced more challenges in demonstrating compassion to students during online teaching. Educators in both countries encountered poor internet connectivity, lack of interaction and engagement with students, stress, and anxiety. Opportunities created by the COVID-19 pandemic comprise exploring and learning online teaching tools, producing online teaching and learning materials, conducting research, and writing research papers for publication. Recommendations for addressing online teaching challenges and suggestions for future research are also discussed.